PENINGKATAN KUALITAS PRODUK PLAFON MENGGUNAKAN METODE SIX SIGMA DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Fattra ramadhan; Ari zaqi al-faritsy (JOURNAL SAINS STUDENT RESEARCH, 2024)
Companies engaged in the production of PVC ceilings experience 6.5% defects per day, so it is necessary to control quality. Problem solving using Six Sigma method with DMAIC (Define, Measure, Analyze, Improve, Control) stages by using FMEA (Failure Mode and Effect Analysis) concept. Found 5 types of defects in the PVC ceiling production process in the defined stage. The measure stage obtained all types of defects are above the control limit based on the P-Chart diagram and the DPMO calculation obtained an average value of 12,995 with a sigma level of 3.73 which shows the sigma value is below the international industry sigma standard value. The analyze stage found that 50.3% of defects occurred in sticker defects less adhesive based on the Pareto diagram. The improve stage obtained the highest RPN value of 240 on the burnt or charred defect, using the 5W + 1H approach, the improvement plan that can be done is to create a production process SOP and employee training in using the machine. Keywords: six sigma; Quality Control; and Failure Mode Effect Analysis (FMEA)